Brucella endocarditis: diagnostic challenges - Christelle G Ephrem; Madonna J Matar; Gaelle C Chalhoub; Wafaa G Greige (Journal of Infection in Developing Countries)
Introduction: Brucellosis is a multisystemic infectious disease, which can manifest as endocarditis. Diagnosis can be challenging.